(untitled) (Revista de Investigaciones Universidad del Quindío, 2023)
In this research, the effects of different nutrient source used for soil fertilization were detected on cooking characters of chickpea varieties. The field experiment was conducted in 2020 growing seasons. The experiment was designed randomized complete blocks in split plots with three replications. In study, it was used Arda, Gokce and local chickpea varieties in main plots. Four organic manures, one biofertilizer and chemical fertilizer (T0: control group, T1: 5 t.ha-1 ovine manure, T2: 5 t.ha-1 cattle manure, T3: 10.000 cc ha-1 liquid vermicompost, T4: 3 t.ha-1 chicken manure, T5: bacteria (Rhizobium ciceri) and T6: 50 kg ha-1 N, 90 kg ha-1 P) were in the sub plots. Comparison of two-way ANOVA test showed that fertilization treatments were no significant for all seed technological characters except for cooking time. Two-way ANOVA test revealed that chickpea varieties was determined superior than treatment and variety * treatment interaction on all characters except for swelling capacity and index. Dry weight, wet weight, dry volume, wet volume and hydration capacity traits varied depending on varieties. The liquid vermicompost treatment (Arda: 38.67 min) and chemical fertilizer (local variety: 40.00 min) showed the shortest cooking time than the other nutrient sources. On the contrary, local variety had the longest cooking time in ovine manure.